Ice accretion on circular cylinder in relation to its diameter. Issue 1 (February 2017) - Virk, Muhammad S
Numerical study of atmospheric ice accretion on circular cylinder is carried out to understand the relation between cylinder diameter and resultant ice accretion. To validate the numerical model, results are compared with the experimental data and a good agreement is found. Numerical study shows that change in cylinder diameter significantly affects the air and droplet behavior that results a change in ice growth along cylinder. A detailed parametric study is carried out for different droplet sizes and cylindrical diameters. Results show a decrease in droplet collision efficiency and ice growth with the increase in cylinder diameter.